Methodology of a rational body position control of a sprinter during the race - Katenkov, A. N. (The Russian Journal of Physical Education and Sport, 2016)
Annotation. A high level of dynamical character of sports achievements demands a constant development of sports training content among runners. According to many specialists in athletics, one of the prospective directions of sportsmanship renewal is pedagogical conditions creation and use, which don`t let a sportsman make incorrect actions, which distort a rational technique of the running steps. Materials. A distinctive feature of sprint is a maximum nervous-muscular tension, which demands great muscular energy in a minimum short time period and it doesn`t let a sportsman concentrate on the fulfilled motor acts fulfillment. It demands special technologies creation, the use of which provides an objective control the running steps parameters. Getting urgent information about the character of movements helps sprinter to react timely on the appearing motional problem of motional actions characteristics correction, which increase their effectiveness. Research methods: scientific-methodical literature analysis, summarizing and systematization, testing, projection and construction, pedagogical experiment, statistical data manipulation. Results. The article presents a simple and informative device for a control and timely correction of sprinter`s oscillatory movements amplitudemagnitude in front-back direction. Projected construction helps to set a feedback and get urgent information about body position in space, which influences the result of competitive activity. This device provides acoustical signal influence on the second signaling system and it helps a sportsman without any additional intellectual and volitional efforts correct parts of the body position during the competitive distance running. Conclusion. The results of the pedagogical experiment showed the effectiveness of the offered by the author methodology of a sprinter`s oscillatory body movements pedagogical control and correction in front-back direction on the basis of an effective device, the use of which provides objective indices getting according to one of the most important parameters of the running steps - amplitude magnitude of oscillatory body movementsin front-back direction. This construction use provides effectiveness increase of the training and competitive activity.